(untitled) (TEST Trento Student Law Review, 2021)
This article revisits the United States Supreme Court case, Addington v. Texas, in which the Court held that the Fourteenth Amendment requires a "clear and convincing" standard for indefinite involuntary civil commitment to a state mental hospital. The Court should have applied a reasonable-doubt standard to involuntary civil commitments, not a "clear and convincing" standard, violating patients’ liberty interests. Moreover, a "clear and convincing" standard misuses states’ parent and police powers, as it hurts patients’ health and subverts public safety. Last, the Court should leave the problem of the unreliability of professional psychiatric opinions to experts and the legislature. Given that COVID-19 swept the nation, disproportionately harming psychiatric patients, it is critical to revisit Addington v. Texas to protect some of the most vulnerable people.